Stress, Anxiety, Binge Drinking, and Substance Use Among College Student-Athletes: A Cross-Sectional Analysis - Brandon A. Knettel; Emily M. Cherenack; Courtney Bianchi-Rossi (University of Kansas Libraries, 2021)
The immense pressure faced by college student-athletes to balance participation in sports with other responsibilities can contribute to unhealthy coping behaviors including alcohol and drug use. We administered online surveys to 188 college student-athletes to examine stress, athletics-related anxiety, and perceived control of stress as predictors of binge drinking, substance use, and associated risk behaviors. Participants rated athletics as the second greatest source of stress in their lives, trailing only academics. Athletics-related anxiety was a significant predictor of cannabis use and substance-related risk behaviors, and represents an understudied area in the literature. Reports of alcohol and drug use in our sample were comparable to national surveys of student-athletes, but opioid misuse was troublingly high. Participants over the age of 21 and males were more likely to report substance use and risk behaviors. Athletes are susceptible to orthopedic injury and associated pain, which may lead to early exposure to opioids with high potential for abuse. Interventions for this population must target social contributors to substance use among student-athletes, opioid prescription and misuse as a gateway to opioid use disorders, and untreated anxiety as a potential driver of substance use, including anxiety associated with athletic performance.